(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
Understanding the intricate relationship between macroeconomic factors and logistics performance is of paramount importance in today’s globalized economy. Efficient logistics operations are not only crucial for facilitating international trade but also serve as a cornerstone for driving economic growth and fostering competitiveness on the global stage. The Logistics Performance Index (LPI), developed by the World Bank, stands as a vital tool for assessing the efficacy of logistics infrastructure and procedures in facilitating the seamless movement of goods across borders. In this study, we delve into the nexus between macroeconomic indicators—namely Gross Domestic Product (GDP), Foreign Direct Investment (FDI), Inflation Rate, and Trade (TRD) and the Logistics Performance Index, aiming to unravel the underlying dynamics that shape logistical efficiency and trade facilitation. By analyzing data from 139 countries in 2022 and employing regression analysis, we unravel the complexities of how these macroeconomic variables interact with logistics performance. The findings reveal intriguing insights, emphasizing the substantial positive impact of Foreign Direct Investment (FDI) and trade openness on the Logistics Performance Index. While FDI fosters improvements in logistics infrastructure and technology, trade openness enhances logistical efficiency through streamlined customs procedures and trade facilitation measures. Conversely, the influence of Gross Domestic Product (GDP) on logistics performance was found to be negligible, suggesting that other factors play a more significant role in shaping logistical efficiency. Moreover, the analysis sheds light on the nuanced relationship between the Inflation Rate and the Logistics Performance Index, with changes in inflation showing low significant impact on logistical efficiency within the scope of this study. However, further exploration is warranted to uncover potential contextual nuances and long-term effects of inflation dynamics on logistical operations. This study underscores the critical importance of considering macroeconomic factors in logistics planning and policymaking.